2022
DOI: 10.1115/1.4054640
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Characterization of Cell Aggregation During and After Inkjet-Based Bioprinting of Cell-Laden Bioink

Abstract: Recently, 3D bioprinting techniques have been broadly recognized as a promising tool to fabricate functional tissues and organs. The bioink used for 3D bioprinting consists of biological materials and cells. Because of the dominant gravitational force, the suspended cells in the bioink sediment resulting in the accumulation and aggregation of cells. This study primarily focuses on the quantification of cell sedimentation-induced cell aggregation during and after inkjet-based bioprinting. The major conclusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As the biomaterial inks become more complex, however, an increased difficulty in printing may arise. Studies have shown that the aggregation of cells and other ink additives can become sufficient to clog the nozzle during long prints resulting in decreased print quality or the inability to print entirely [ 76 ]. Although this phenomenon can be mitigated to some degree using inkjet circulation or by ink additives such as polyvinylpyrrolidone, the pursuit of enhanced ink additives and capabilities must be carefully balanced to ensure that printability remains sufficient to allow a high level of architecture control [ 77 ].…”
Section: Emerging Biomedical Advancesmentioning
confidence: 99%
“…As the biomaterial inks become more complex, however, an increased difficulty in printing may arise. Studies have shown that the aggregation of cells and other ink additives can become sufficient to clog the nozzle during long prints resulting in decreased print quality or the inability to print entirely [ 76 ]. Although this phenomenon can be mitigated to some degree using inkjet circulation or by ink additives such as polyvinylpyrrolidone, the pursuit of enhanced ink additives and capabilities must be carefully balanced to ensure that printability remains sufficient to allow a high level of architecture control [ 77 ].…”
Section: Emerging Biomedical Advancesmentioning
confidence: 99%
“…A recent study primarily focused on the comprehensive quantification of cell sedimentation‐induced aggregation during and following inkjet‐based bioprinting. [ 217 ] It was revealed that extending the printing time by 60 min results in a significant increase in the percentage of cells forming aggregates at the bottom of the bioink reservoir (i.e., from 3.6% to 54.5%). This escalation underscores the profound challenge posed by cell aggregation in the realm of 3D bioprinting.…”
Section: Bioprintingmentioning
confidence: 99%
“…Later, the same group presented a study characterizing cell aggregation both during and after the inkjet-based bioprinting process. 46 It was observed that the percentage of cells forming cell aggregates at the bottom of the bioink reservoir increased significantly from 3.6% to 54.5% within 60 min of printing time. In addition, a huge percentage of cells have been found to adhere to form cell aggregates both within the inkjet nozzle during printing and formed microspheres after printing.…”
Section: Introductionmentioning
confidence: 95%
“…It was reported that only within 40 min of printing time, almost all of the cells within the bioink containing 0.5% (w/v) sodium alginate have sedimented to the bottom, significantly increasing the cell concentration and facilitating cell aggregation. Later, the same group presented a study characterizing cell aggregation both during and after the inkjet-based bioprinting process . It was observed that the percentage of cells forming cell aggregates at the bottom of the bioink reservoir increased significantly from 3.6% to 54.5% within 60 min of printing time.…”
Section: Introductionmentioning
confidence: 99%